2022
DOI: 10.3389/fcvm.2022.919823
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Examination of an Explanted Heart in a Long-Term Responder to Cardiac Stereotactic Body Radiotherapy (STereotactic Arrhythmia Radioablation)

Abstract: Cardiac stereotactic body radiotherapy is an emerging treatment method for recurrent ventricular tachycardia refractory to invasive treatment methods. The single-fraction delivery of 25 Gy was assumed to produce fibrosis, similar to a post-radiofrequency ablation scar. However, the dynamics of clinical response and recent preclinical findings suggest a possible different mechanism. The data on histopathological presentation of post-radiotherapy hearts is scarce, and the authors provide significantly different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Dose effect. Several studies evaluated any dose effect on biological consequences, radiation-induced toxicity, and therapeutic efficacy (11,14,15,17,18,20,22,29). In terms of biological effects, the following results were reported: i) increased expression of connexin 43 is evident only after STAR with dose ≥10 Gy (11), ii) transmural scarring of the heart is recorded only with STAR doses ≥32.5 Gy (14), while iii) transmural scarring of the target can be observed only after STAR doses >30 Gy (15).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dose effect. Several studies evaluated any dose effect on biological consequences, radiation-induced toxicity, and therapeutic efficacy (11,14,15,17,18,20,22,29). In terms of biological effects, the following results were reported: i) increased expression of connexin 43 is evident only after STAR with dose ≥10 Gy (11), ii) transmural scarring of the heart is recorded only with STAR doses ≥32.5 Gy (14), while iii) transmural scarring of the target can be observed only after STAR doses >30 Gy (15).…”
Section: Resultsmentioning
confidence: 99%
“…Different experimental models were used in the analyzed studies, and in particular: living rabbits (10,11), mini-pigs (12,14,15), pigs (18, 20, in vivo 37: 963-971 (2023) • Fibrotic scar in the irradiated region (case 3) AF: Atrial fibrillation; AR: arrhythmia; AV: atrioventricular; CT: computed tomography; CCT: cardiac computed tomography; EAM: electroanatomical mapping; ICD: implantable cardioverter defibrillator; MRI: magnetic resonance imaging; RT: radiotherapy; STAR: stereotactic arrhythmia radioablation; VT: ventricular tachycardia. 21,25), dogs (19) or dogs and pigs (13,22), explanted and reperfused pig hearts (16,17), explanted human hearts of non-ischemic cardiomyopathy patients after STAR in the context of transplantation (2,29), and human hearts evaluated postmortem (24,29). The experimental methods were also heterogeneous between studies including myocardial infarction induced by microsphere injection in coronary arteries (10,18) and STAR on healthy hearts (11,14,16,17,18,20,22).…”
Section: Discussionmentioning
confidence: 99%
“…(1) vacuolization, fibrosis and necrosis after doses exceeding 30 Gy [23,24], and (2) protein changes due to notch activation resulting in increased conduction velocity [25,26]. Clinically, patients may respond to STAR within a few days showing no fibrosis in the treated area [25,27,28] or up to weeks and months later with small pathological lesions [29,30]. Further understanding of these complex interactions and variable treatment effects may eventually lead to different concepts and requirements for target definition, treatment planning and treatment precision.…”
Section: Editorial Precision Requirements In Stereotactic Arrhythmia ...mentioning
confidence: 99%
“…In cardiomyocytes, the cell surface receptor Notch reprograms/reactivates cells contributing to electrical stability. [16][17][18] 4.5 Rationale for further investigational study Despite the successes that have been reported in the literature, a consensus and generalizable framework does not yet exist for administering STAR. Without consistency in process and treatment delivery, the size, and locations of identified VT ablation targets can vary tremendously between patients and ablation facilities, making difficult proper analysis of the successes and failures of cardiac SBRT.…”
Section: Mechanism Of Actionmentioning
confidence: 99%